Isotopic geochronology of granitic rocks from the Central Iberian Zone: comparison of methodologies - Antunes, I.M.H.R. (2011)
Five granitic rocks, concentrically disposed from core to rim, were distinguished in the Castelo Branco pluton. U-Pb-Th electron microprobe monazite ages from granitic rocks are similar and ranging between 297-303 Ma. The granitic rocks from Castelo Branco pluton are 310 ± 1 Ma old, obtained by U-Pb (ID-TIMS) in separated zircon and monazite crystals, indicating a similar emplacement age for all granitic rocks of the pluton. Initial 87Sr/86Sr isotopic ratios and εNd310 and δ18O values suggest three distinct pulses of granitic magma and that they are derived from partial melting of heterogeneous metasedimentary materials. The other granitic rocks are related by magmatic differentiation and show small variations in (87Sr/86Sr)310, εNd310 and δ18O. The granitic pluton of Castelo Branco shows a rare reverse zoning.